Book Review: Jagdish Bhagwati and Arvind Panagariya, eds, Why Growth Matters: How Economic Growth in India Reduced Poverty and the Lessons for other Developing Countries and Jean Dreze and Amartya Sen, eds, An Uncertain Glory: India and Its Contradictions. (June 2014) - Jenkins, Rob
Jagdish Bhagwati and Arvind Panagariya, eds, Why Growth Matters: How Economic Growth in India Reduced Poverty and the Lessons for other Developing Countries. New York, NY: Public Affairs. 2013. 302 pages. US$ 28.99. Jean Dreze and Amartya Sen, eds, An Uncertain Glory: India and Its Contradictions. Princeton, NJ: Princeton University Press. 2013. 446 pages. US$ 22.95.